VvSWEET7 Is a Mono- and Disaccharide Transporter Up-Regulated in Response to Botrytis cinerea Infection in Grape Berries - Breia, Richard; Conde, Artur; Pimentel, Diana; Conde, Carlos; Fortes, Ana Margarida; Granell, Antonio; Gerós, Hernâni (Frontiers in Plant Science, 2020)
The newly-identified SWEETs are high-capacity, low-affinity sugar transporters with important roles in numerous physiological mechanisms where sugar efflux is critical. SWEETs are desirable targets for manipulation by pathogens and their expression may be transcriptionally reprogrammed during infection. So far, few plant SWEET transporters have been functionally characterized, especially in grapevine. In this study, in the Botrytis-susceptible variety “Trincadeira”, we thoroughly analyzed modifications in the gene expression profile of key SWEET genes in Botrytis cinerea-infected grape berries. VvSWEET7 and VvSWEET15 are likely to play an important role during fruit development and Botrytis infection as they are strongly expressed at the green and mature stage, respectively, and were clearly up-regulated in response to infection. Also B. cinerea infection down-regulated VvSWEET17a expression at the green stage, VvSWEET10 and VvSWEET17d expression at the veraison stage and VvSWEET11 expression at the mature stage. VvSWEET7 was functionally characterized by heterologous expression in Saccharomyces cerevisiae as a low-affinity, high-capacity glucose and sucrose transporter with a Km of 15.42 mM for glucose and a Km of 40.08 mM for sucrose. VvSWEET7-GFP and VvSWEET15-GFP fusion proteins were transiently expressed in Nicotiana benthamiana epidermal cells and confocal microscopy allowed to observe that both proteins clearly localize to the plasma membrane. In sum, VvSWEETs transporters are important players in sugar mobilization during grape berry development and their expression is transcriptionally reprogrammed in response to Botrytis infection.